Arabidopsis thaliana EPOXIDE HYDROLASE1 (AtEH1) is a cytosolic epoxide hydrolase involved in the synthesis of poly‐hydroxylated cutin monomers. Issue 1 (12th May 2017) - Pineau, Emmanuelle; Xu, Lin; Renault, Hugues; Trolet, Adrien; Navrot, Nicolas; Ullmann, Pascaline; Légeret, Bertrand; Verdier, Gaëtan; Beisson, Fred; Pinot, Franck
Summary: Epoxide hydrolases (EHs) are present in all living organisms. They have been extensively characterized in mammals; however, their biological functions in plants have not been demonstrated. Based on in silico analysis, we identified AtEH1 (At3g05600), a putative Arabidopsis thaliana epoxide hydrolase possibly involved in cutin monomer synthesis. We expressed AtEH1 in yeast and studied its localization in vivo . We also analyzed the composition of cutin from A. thaliana lines in which this gene was knocked out. Incubation of recombinant AtEH1 with epoxy fatty acids confirmed its capacity to hydrolyze epoxides of C18 fatty acids into vicinal diols. Transfection of Nicotiana benthamiana leaves with constructs expressing AtEH1 fused to enhanced green fluorescent protein (EGFP) indicated that AtEH1 is localized in the cytosol. Analysis of cutin monomers in loss‐of‐function Ateh1‐1 and Ateh1‐2 mutants showed an accumulation of 18‐hydroxy‐9, 10‐epoxyoctadecenoic acid and a concomitant decrease in corresponding vicinal diols in leaf and seed cutin. Compared with wild‐type seeds, Ateh1 seeds showed delayed germination under osmotic stress conditions and increased seed coat permeability to tetrazolium red. This work reports a physiological role for a plant EH and identifies AtEH1 as a new member of the complex machinery involved in cutin synthesis.